PEMANFAATAN PURE UBI JALAR KUNING DAN AMPAS KELAPA KERING DALAM PEMBUATAN KUKIS - TUSI WANTI; NETTI HERAWATI; SHANTI FITRIANI (Jurnal Sagu, 2019)
The objective of this study was to obtain exact formulation of combination of yellow sweet potato puree anddry coconut dregs based on quality standards for making cookies. This study used a completely randomizeddesign (RAL) with five treatments and three replications. The treatments of yellow sweet potato puree anddried coconut dregs on wheat flour consists of UK1 (70% yellow sweet potato puree and 0% dried coconutdregs), UK2 (65% pure yellow sweet potato and 5% dried coconut dregs), UK3 (60% yellow sweet potatopuree and 10% dried coconut dregs), UK4 (55% yellow sweet potato puree and 15% dried coconut dregs),and UK5 (50% yellow sweet potato puree and 20% dried coconut dregs). Data were statistically analyzedusing ANOVA and DNMRT at 5% level. The result of analysis of variance showed that the formulation ofcombination of yellow sweet potato puree, dry coconut dregs, and wheat flour had significantly affectedwater, ash, fat, protein, crude, and carbohydrate content as well sensory assessment. The results showed thatthe selected treatment was UK3 with which got a moisture content of 3,80%, ash content of 1,87%, fat contentof 24,90%, protein content of 7,49%, crude fiber of 4,00%, and carbohydrate content of 61,93% with thesensory description yellow in color, yellow sweet potato and coconut pulp flavour, yellow sweet potato andcoconut pulp taste, and crispy in texture and be liked overall by panelists.